Adding value to myocardial perfusion SPECT/CT studies that include coronary calcium CT: Detection of incidental pulmonary arterial dilatation. Issue 32 (August 2018) - Marcus, Charles; Santhanam, Prasanna; Kruse, Matthew J.; Javadi, Mehrbod S.; Solnes, Lilja B.; Rowe, Steven P.
Abstract : Abstract: The aim of the present study was to evaluate the incidence of undiagnosed pulmonary arterial dilatation using the gated computed tomography (CT) images acquired in patients with an otherwise normal 99m Tc-sestamibi single-photon-emission CT (SPECT)/CT myocardial perfusion study. This was a retrospective review of 200 consecutive patients (100 men, mean age 58.7 years) who underwent a myocardial perfusion 99m Tc-sestamibi SPECT/CT study with normal perfusion and with gated CT images acquired for coronary calcium scoring. The CT images were reviewed using a previously validated mean main pulmonary artery diameter (mPAD) measurement method which has been correlated with pulmonary arterial hypertension (PAH). Clinical information on multiple comorbidities was also retrieved. Previously reported mPAD cutoffs (>29.5 and >31.5 mm) were used to stratify patients. Indications for the study included dyspnea on exertion (58.9%), preoperative workup (22.3%), and chest pain (13.9%). The mean mPAD measurement was 26.3 mm (±0.5). There was a significant correlation between body mass index and mPAD (correlation coefficient [ρ]: 0.28; P < .001). About 23% (46/200) of patients had mPAD > 29.5 mm and 15.0% (30/200) of patients had mPAD > 31.5 mm. From previous work, these cutoffs have a sensitivity and specificity for PAH of 70.8%, 79.4% and 52.0%, 90.2%, respectively. Among patients undergoing a preoperative myocardial perfusion study, 35.6% (16/45) patients had mPAD > 29.5 mm and 26.7% (12/45) patients had mPAD > 31.5 mm. There was a higher prevalence of congestive heart failure (62.5% vs 19.6%; P < .001) and hypertension (78.3% vs 21.7%; P < .02) in patients with mPAD > 29.5 mm. Similarly, there was a high prevalence of congestive heart failure ( P < .001), hyperlipidemia ( P < .04), and hypertension ( P < .04) in patients with mPAD > 31.5 mm. Incidental pulmonary arterial dilatation (mPAD ≥ 29.5 mm) can be detected in a large number of patients with normal myocardial perfusion scintigraphy and correlates with multiple different comorbidities. The mPAD can be measured in all patients undergoing gated imaging as part of a myocardial perfusion study, and PAH may be considered as an alternative explanation for symptoms in some patients without perfusion deficits. The data to make this potential diagnosis is already being acquired and represents an opportunity to add value to the interpretations of otherwise negative myocardial perfusion studies.